2005
DOI: 10.1111/j.1472-8206.2005.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Captopril–furosemide survival study in experimental heart failure

Abstract: The strategy of diuretic drug administration remains to be defined in heart failure as experimental and clinical evidence have clearly established the benefit of neurohormonal blockade. The impact of addition of diuretic treatment to angiotensin-converting enzyme inhibition on survival remains to be demonstrated. The objectives of the study were to evaluate cardiovascular and renal effects of addition of diuretic treatment to captopril (2 g/L, in drinking water), on survival, on the experimental model of heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…A retrospective analysis of a possible coherency between the diuretic effect and the mortality in the furosemide treated animals showed that animals subjected to a larger diuretic effect tended to show a poorer survival rate. Moreover, the furosemide dose in our study (10 mg/kg/d) was not high compared to those in previous experimental studies, ranging from 4 mg [24] to 30 mg [12,32], 40 mg, 80 mg [20] and 100 mg/(kg day) [12]. Since the incidence of volume depletion under furosemide treatment was previously reported to be dose dependent [33] the adequate dose which was used in our study did not elicit an especially large diuresis.…”
Section: Volume Statuscontrasting
confidence: 47%
“…A retrospective analysis of a possible coherency between the diuretic effect and the mortality in the furosemide treated animals showed that animals subjected to a larger diuretic effect tended to show a poorer survival rate. Moreover, the furosemide dose in our study (10 mg/kg/d) was not high compared to those in previous experimental studies, ranging from 4 mg [24] to 30 mg [12,32], 40 mg, 80 mg [20] and 100 mg/(kg day) [12]. Since the incidence of volume depletion under furosemide treatment was previously reported to be dose dependent [33] the adequate dose which was used in our study did not elicit an especially large diuresis.…”
Section: Volume Statuscontrasting
confidence: 47%
“…It could be hypothesised that pharmacotherapy and cardiac remodelling over the course of several months accounted for the decrease in TR and eventual complete resolution of clinical signs. Several drugs including association of angiotensin‐converting enzyme (ACE) inhibitor and loop diuretics, as used in this study, have been proven to help in cardiac remodelling in experimental model of heart failure in rats (Mougenot and others 2005). It could therefore be hypothesised that chronic use of the combination of furosemide (loop diuretic) and benazepril (ACE inhibitor) may have elicited some cardiac remodelling, buffering the effect of atrial dilatation and ventricular eccentric hypertrophy observed in the natural course of tricuspid regurgitation.…”
Section: Discussionmentioning
confidence: 99%